Enfermedad de Grover, una patología ampollar poco frecuente: a propósito de 2 casos - Moya G., Nicolás; Cortés G., Andrea; Morales H., Claudia; Vera G., Valentina (Revista Hospital Clínico Universidad de Chile, 2018)
Introduction: Grover’s disease (GD) or transient acantholytic dermatosis, is a papulovesicular pruritic disease of unknown etiology. It´s most important histopathological finding is the presence of focal acantholysis. The incidence has not been firmly established. Case report: We report two cases of papulovesicular rashes, the first one in a 79 year old man with good response to second line treatment and the second one, in a 30 year old woman. Both with different suspected triggering factors. Comment: GD predominates in white men with an average age of presentation of 61. Clinically, it presents as erythematous papules, crusted-papule and is usually pruritic. The etiopathology is still unknown, but it is associated with triggers such as: ultraviolet radiation (UVR), ionizing radiation, heat, sweat, friction and chemotherapy. Acantholysis is the classic histological finding. Management includes general measures, topical corticosteroids, calcineurin inhibitors, tretinoin, calcipotriene and antihistamines. In refractory cases, second-line treatment is used: oral isotretinoin, systemic corticosteroids and phototherapy. Paradoxically, phototherapy can also trigger GD. Conclusions: Due to the low prevalence of GD in Chile, 2 new cases are provided to the literature. In both cases, the diagnostic presumption was based on an exhaustive clinical history, confirmed by histopathological findings.